Detection of Tick-Borne Pathogens in Ticks from Dogs and Cats in the Yamagata Prefecture of Japan in 2018 - Seto, Junji; Tanaka, Shizuka; Kawabata, Hiroki; Ito, Yasuki; Ikeda, Tatsuya; Mizuta, Katsumi (Japanese Journal of Infectious Diseases, 2021)
Companion animals can become infected with tick-borne diseases (TBDs) becoming a reservoir for human transfer, thereby damaging human health. To evaluate whether companion animals are infested with ticks harboring human TBD pathogens, we detected TBD pathogens in ticks collected from dogs and cats brought to animal hospitals in the Yamagata prefecture of Japan. An investigation of 164 adult ticks collected from 88 dogs and 41 cats between March and July 2018 revealed that this region was dominated by three tick species, Ixodes ovatus (n = 95, 57.9%), Ixodes nipponensis (n = 37, 22.6%) and Haemaphysalis flava (n = 10, 6.1%). To evaluate their pathogenic potential, we went on to test each tick for spotted fever group rickettsiae, Lyme disease borreliae, relapsing fever borreliae, tick-borne encephalitis virus, and Huaiyangshan banyangvirus (formerly SFTS virus). Our results identified two I. ovatus ticks infected with Borrelia miyamotoi, which causes emerging relapsing fever; several I. nipponensis ticks infected with Rickettsia monacensis, which cause rickettsiosis; and several Ixodes persulcatus ticks infected with Rickettsia helvetica, which can also cause rickettsiosis. These results suggest that dogs and cats, and veterinary professionals and pet owners, in the Yamagata prefecture have some risk of exposure to several TBDs. This means that there should be continuous monitoring and reporting of TBDs, even those known to be uncommon in Japan, in both companion animals and humans to ensure the health and safety of both humans and animals in Japan.